Phase transition system: Novel oral in-situ gel - Nagarwal R.C.; Pandit J.K. (My University, 2025)
Inspite of the various impediments in the bioavailability of orally delivered drugs, oral dosage forms, both solid and liquid, occupy a center stage in the therapeutic regimen of diseases. However, liquid dosage forms are more prone to low bioavailability because of their quick transit from the stomach/ duodenum. This could be a serious problem for drugs, which are absorbed from these sites of the GIT. The gastric retention of an oral liquid formulation could be successfully augmented substantially through a strategy of liquid in-situ gelling system. Natural polymers like alginate, gellan and chitosan can undergo sol to gel transformation in the presence of either divalent cations or due to a change in pH. The gel so formed, being lighter than gastric fluids, floats over the stomach contents and is retained there in for periods upto 24 hours. The in-situ gel formation enhances the local or systemic bioavailability of the administered drug. This concept is a redesign of liquid oral dosage form, which fulfills the requirement for a sustained release liquid preparation. This review discusses the various aspects associated with the in-situ gelling systems and their therapeutic applications. © 2008 Bentham Science Publishers Ltd.